Investigation of depression frequency and quality of life in couples with infertility complaints in Turkey - Batuhan Turgay; Ruşen Aytaç (Scientific Reports)
Abstract Our objective was to examine the prevalence of depression and quality of life in couples diagnosed with infertility, as well as to determine the factors correlated with these variables. This cross-sectional study included 165 couples who requested assistance at a university-affiliated infertility center. The participants completed the Beck Depression Inventory (BDI) and Fertility Quality of Life (FertiQoL) questionnaires at their initial visit. The estimated factors potentially linked to quality of life and depressive state were documented, and their relationships with the questionnaire results were examined. The average total FertiQoL scores of women were substantially lower, and the BDI scores were significantly higher than those of men. Compared with the primary infertility cohort, the secondary infertility cohort presented superior outcomes. No relationship existed between the cause of infertility and the scores obtained from the FertiQoL and BDI questionnaires. A total of 90.2% of women, 92% of men, and 90.9% of all patients presented scores on the BDI that were not suggestive of clinical depression levels. A negative association was identified between BDI scores and FertiQoL scores, and no factors significantly influenced overall FertiQoL scores on the basis of regression analysis. The FertiQoL questionnaire can be used to assess the quality of life of both genders precisely. In particular, a decline in women’s quality of life and increased depression scores can reduce women’s motivation for treatment; therefore, clinicians need to consider this situation.